THE AMBROSIANUS MANUSCRIPT AND ITS VARIANTS: A STUDY IN COMPARISON WITH THE GALATIAN ETHIOPIC MANUSCRIPT - Bazezew, Fikremariam (Journal of Oriental Studies, 2025)
This article offers a detailed comparative analysis of two significant Ethiopic manuscripts the Maqala Mikael 167, a 16th-century document, and the Ambrosiana manuscript, which dates back to the 14th century. Both manuscripts contain important versions of the Epistles of Saint Paul, yet they present some crucial differences that shed light on the transmission and preservation of these texts within the Ethiopic tradition. The primary focus of the study is the identification of notable omissions in the Ambrosiana manuscript when compared to the Maqala Mikael 167. These discrepancies are not only significant in the context of textual variations but also crucial for understanding the development of the Epistles' textual tradition over time. By examining these omissions and the manuscript's specific details, the article aims to enhance the critical edition of the Epistles, offering valuable insights into the historical and textual evolution of these ancient Christian writings. Additionally, the study highlights the importance of the Maqala Mikael 167 as a completer and more reliable source for the critical analysis of Saint Paul’s Epistles, providing a more comprehensive version of the texts. At the same time, the Ambrosiana manuscript’s historical and cultural significance is acknowledged, as it represents an earlier stage in the transmission of the Epistles within Ethiopic Christianity. This comparative approach helps deepen our understanding of the complexities involved in the preservation of sacred texts in Ethiopic Christianity, contributing to ongoing scholarly efforts in textual criticism. Keywords: Ethiopic manuscript, Textual omissions, comparison, Codex Ambrosianus, Textual criticism